Electronic health records : an audit and internal control guide - Busch, Rebecca S. (Wiley, 2008)
This book focuses on the infrastructure of an electronic health record and the impact that the government's new criteria will have on the private and public marketplace. Walking readers through what to look for in a health care record management system, it includes implementation tips and other helpful guidance.